Iron overload and Hepcidin overexpression could play a key role in COVID infection, and may explain vulnerability in elderly, diabetics, and obese patients - Banchini, Filippo; Vallisa, Daniele; Maniscalco, Pietro; Capelli, Patrizio (Acta Biomedica Atenei Parmensis, 2020)
Background: The COVID epidemic hit like a tsunami worldwide. At the time of its arrival in Italy, available literary data were meager, and most of them concerned its epidemiology. World Health Organization proposed guidelines in march 2020, a strategy of treatment has been developed, and a significant number of subsequent articles have been published to understand, prevent, and cure COVID patients. Methods: From the observation of two patients, we performed a careful analysis of scientific literature to unearth the relation between COVID infection, clinical manifestations as pneumonia and thrombosis, and to find out why it frequently affects obese, diabetics, and elderly patients. Results: The analysis shows that hepcidin could represent one of such correlating factors. Hepcidin is most elevated in older age, in non-insulin diabetics patients and in obese people. It is the final target therapy of many medicaments frequently used. Viral disease, and in particular SARS-CoV19, could induce activation of the hepcidin pathway, which in turn is responsible for an increase in the iron load. Excess of iron can lead to cell death by ferroptosis and release into the bloodstream, such as free iron, which in turn has toxic and pro-coagulative effects. Conclusions: Overexpression of hepcidin and iron overload might play a crucial role in COVID infection, becoming potential targets for treatment. Hepcidin could also be considered as a biomarker to measure the effectiveness of our treatments and the restoration of iron homeostasis the final intent. (www.actabiomedica.it)